Characterizing university faculty's perceptions of scholarly teaching in engineering education: a social realistic perspective. Issue 3 (16th April 2021) - Zhuang, Tengteng; Huang, Ya-Ting
ABSTRACT: Against the backdrop of prevalent student attrition in engineering education, this study draws upon Margaret Archer's social realistic theory and offers a close-up analysis of how structural and cultural factors interplay to affect Chinese university engineering faculty members' perceptions of and agency in practicing 'scholarly teaching'. Incorporating Chinese socio-cultural contexts and the distinctive requirements of engineering education, this study investigates how structural and cultural facilitating factors are overwhelmed by more powerful inhibiting factors in shaping Chinese engineering faculty members' implementation of scholarly teaching. This article argues that such predominance of inhibiting factors results from the stronger role of communicative reflexivity in influencing faculty members' agency than autonomous reflexivity and meta-reflexivity.